DEMOGRAPHIC FACTORS AS PREDICTORS OF LECTURERS’ SOCIAL AND EMOTIONAL INTELLIGENCE: AN EMPIRICAL INVESTIGATION - Praditsang, Mali; Pittiyakul, Panatchakorn (PEOPLE: International Journal of Social Sciences, 2019)
This study was carried to explore the influence of demographic variables in lecturers emotional and social intelligence in social cognitive learning theory was used to explore the influence of demographic factors on lecturers’ social and emotional intelligence. Data were collected from two hundred and thirty (230) lecturers using the valid instrument titled social intelligence scale and emotional intelligence inventory was adopted for data collection. The analysis of data collected was carried out using statistical package for social sciences (SPSS). The findings of the study revealed that age, gender and working condition does not significantly predict lecturers’ social and emotional intelligence. However, it was revealed that salary is a good predictor of lecturers’ social intelligence while it does not predict their emotional intelligence.